Characterization of the AggR Regulon in Enteroaggregative Escherichia coli - Morin, Nicholas (American Society for Microbiology, 2013)
AggR is a transcriptional regulator of enteroaggregative Escherichia coli (EAEC) and has been proposed as the defining factor for typical EAEC strains. Expression of multiple putative virulence factors, including the aggregative adherence fimbriae (AAF), dispersin, the dispersin translocator Aat, and the Aai type VI secretion system, have been found to be regulated by AggR. Here, we confirm the existence of at least 44 AggR-regulated genes using DNA microarray and real-time quantitative reverse transcription-PCR (qRT-PCR); these genes include chromosomal and plasmid-borne loci and 19 previously unsuspected genes. Two previously uncharacterized virulence plasmid-encoded open reading frames (ORFs) (designated ORF3 and ORF4) exhibit significant identity with isoprenoid biosynthesis genes of Bacteria and Archaea. The predicted ORF4 product is closely related to isopentenyl isomerase (IDI) enzymes, whereas the predicted product of the adjacent ORF3 exhibits an aspartate-rich region that is common among trans-isoprenyl phosphate synthases. We show that mutations in these ORFs confer changes in bacterial surface properties. AggR coordinately controls expression of a large number of EAEC genes.